Super table book with mental practice - Dreamland publications (New Delhi : Dreamland publications, 2015)
Super table book with mental practice is a colorful array of mathematical exercises that the young ones would enjoy doing. It equips them with step-by-step guidance that aids in the enhancement of numerical concepts.
Location: 2C
Keywords: Math activity book